2013
DOI: 10.1371/journal.pone.0063026
|View full text |Cite
|
Sign up to set email alerts
|

Novel Compound Heterozygous TMC1 Mutations Associated with Autosomal Recessive Hearing Loss in a Chinese Family

Abstract: Hereditary nonsyndromic hearing loss is highly heterogeneous and most patients with a presumed genetic etiology lack a specific diagnosis. It has been estimated that several hundred genes may be associated with this sensory deficit in humans. Here, we identified compound heterozygous mutations in the TMC1 gene as the cause of recessively inherited sensorineural hearing loss by using whole-exome sequencing in a family with two deaf siblings. Sanger sequencing confirmed that both siblings inherited a missense mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…These families have their origins in Pakistan, Turkey, Tunisia, Iran, Lebanon/Jordan, North America, China, Europe, Sudan and Morocco (Table 2) [23,35,3748]. These 39 mutations are widely distributed throughout the entire coding region of TMC1 .…”
Section: Phenotype and Mutation Spectrum Of Dfnb7/b11 Subjectsmentioning
confidence: 99%
“…These families have their origins in Pakistan, Turkey, Tunisia, Iran, Lebanon/Jordan, North America, China, Europe, Sudan and Morocco (Table 2) [23,35,3748]. These 39 mutations are widely distributed throughout the entire coding region of TMC1 .…”
Section: Phenotype and Mutation Spectrum Of Dfnb7/b11 Subjectsmentioning
confidence: 99%
“…In China, recent studies on TMC1 mutations such as c.589G>A, c.1171C>T (Xue et al, 2013), c.1209G>C (Tao et al, 2013Tao, Xiaoming, Yongchuan, Lei, & Hao, 2013), c.1253T>A (Yali et al, 2014), c.1714G>A (Xue et al, 2015), and c.1979C>T (Jiongjiong et al, 2016) have been reported. All mutations were analyzed by genetic testing of sporadic families without regional specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The protein, which functions as an ion channel or transporter to mediate K+ homeostasis for the normal function of cochlear hair cells, consists of 760 amino acids containing six transmembrane (TM) domains (Xue et al, 2013). TMC1 c.2050G>C (p.D684H) is a missense variant in exon21.…”
Section: Introductionmentioning
confidence: 99%
“…Single-nucleotide polymorphism (SNP) analysis was performed as previously described (Gao et al, 2013): (1) reads were aligned to the NCBI human reference genome (gh19/NCBI 37.1) with SOAPaligner method V2.21; (2) for paired-end reads with duplicated start and end sites, only one copy with the highest quality was retained and the reads with adapters were removed; (3) SOAPsnp V1.05 was used to assemble the consensus sequence and call genotypes; (4) small insertions and deletions (INDELs) detection was used with the Unified Genotyper tool from GATK V1.0.4705.…”
Section: Read Mapping and Variant Detectionmentioning
confidence: 99%
“…Five major steps were taken to prioritize all the high-quality variants among CHD-related genes (Gao et al, 2013): (1) variants within intergenic, intronic, and untranslated regions (UTRs) and synonymous mutations were excluded from later analysis; (2) variants in dbSNP132 (http://www.ncbi.nih.gov/ projects/SNP/), the 1000 Genomes project (1000G, http://www.1000genomes.org), and HapMap project (ftp://ftp.ncbi.nlm.nih.gov/hapmap) were excluded; (3) variants in YH database (http://yh.Genomics. org.cn/) and National Heart, Lung, and Blood Institute (NHLBI) ESP database (http://evs.gs.washington.…”
Section: Filtering and Annotationmentioning
confidence: 99%